A new species of the shore-fly genus Notiphila Fallén, 1810 (Diptera: Ephydridae) from Indonesia - Krivosheina, M.g.; Ozerov, A.l. (Zootaxa, 2015)
A new shore-fly species, Notiphila oksanae sp.n. from Indonesia is described. The new species is similar to the Oriental species Notiphila thaica Krivosheina, 2010 in having many brown stripes on the thorax and in presurstyli broad in lateral view, but differs in 2 facial setae of subequal length, the absence of brown band on anepisternum and the presence of dark band on hind tibia. A key to the presently known Australasian/Oceanian species of the genus Notiphila Fallén, 1810 is given.